Labor market adjustments to population decline: A historical macroeconomic perspective, 1875-2019 - Timon Hellwagner; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
Advanced economies will face population decline in the years and decades to come, particularly among those of working age. Yet, there is little empirical evidence of corresponding labor market implications. Tackling this shortcoming from a historical macroeconomic point of view, we compile a new dataset for sixteen advanced economies, covering demographic and labor market variables on an annual basis from 1875 to 2019. Based on a dynamic, nonlinear econometric model, we identify structural population shocks by using lagged births as external instruments for working-age population inflows and outflows, and trace the economic effects conditionally on the demographic regime. Our results suggest regime-specific differences: First, population decline quickly passes through to the labor market, translating into swifter disinvestment and decline in employment, but the effects of population growth take time. Second, in times of population decline, labor force participation increases as a response to reduced labor supply. Likewise, initially swift disinvestment tendencies decelerate. Consequently, we find only incomplete capital adjustment. Third, despite a declining labor supply, we find neither a decrease in unemployment nor any significant changes in wages as indicators of shortage. Finally, while population decline tends to depress total factor productivity, as also suggested by the literature, our results indicate that negative effects for economic growth are mitigated by increases in participation and the capital-labor ratio. – – In den kommenden Jahren und Jahrzehnten werden Industrienationen mit Bevölkerungsrückgängen, insbesondere im erwerbsfähigen Alter, konfrontiert sein. Dennoch gibt es bisher wenig empirische Evidenz zu entsprechenden Arbeitsmarktimplikationen. Wir adressieren diese Forschungslücke aus einer historischen, makroökonomischen Perspektive und stellen einen neuen Datensatz für sechzehn Industrienationen zusammen, der demografische und ökonomische Variablen von 1875 bis 2019 auf jährlicher Basis enthält. Auf Grundlage der Ergebnisse eines dynamischen, nichtlinearen ökonometrischen Modells und unter Zuhilfenahme verzögerter Geburten als externe Instrumente identifizieren wir strukturelle Bevölkerungsschocks und analysieren die ökonomischen Effekte von Bevölkerungsänderungen in Abhängigkeit des vorherrschenden demografischen Regimes. Unsere Ergebnisse deuten regimespezifische Unterschiede hin: Erstens, Bevölkerungsrückgang wirkt sich im Vergleich zu Bevölkerungswachstum rascher auf den Arbeitsmarkt aus, was sich insbesondere in Rückgängen von Investitionen und Beschäftigung widerspiegelt. Zweitens, in Zeiten von Bevölkerungsrückgang beobachten wir aber in der Folge und als Reaktion auf das sinkende Arbeitsangebot eine steigende Erwerbsbeteiligung sowie sich abschwächende Rückgänge von Investitionen. Drittens, trotz des sinkenden Arbeitsangebots finden wir weder einen Rückgang der Arbeitslosigkeit noch einen Anstieg von Löhnen. Während sich Bevölkerungsrückgang tendenziell negativ auf die Produktivität auswirkt, wie auch in der Literatur argumentiert wird, deuten unsere Ergebnisse darauf hin, dass daraus resultierende negative Effekte auf das Wirtschaftswachstum durch eine erhöhte Erwerbsbeteiligung und Kapitalintensität abgefangen werden.
Keywords: J11; J21; E22; E24; 330; Population decline; labor market adjustments; historical dataset; smooth transition regression; proxy VAR